The Influence of Halal Brand Awareness and Halal Label on Purchase Decisions at Saudi Stores in Banda Aceh City with Religiosity as a Moderating Variable - Suci Rahmadhani; Novi Indriyani Sitepu; Hendra Halim; Yenni Samri Juliati Nasution (International Journal of Kita Kreatif, 2026)
This study aims to quantify the influence of halal brand awareness and halal label on purchase decision at Saudi Store in Banda Aceh City with religiosity being a moderation variable. In this study, primary and secondary data collected were used to support the analysis process. The population of this study were Saudi Store consumers domiciled in Banda Aceh City, with a total sample of 150 respondents. The number of samples was determined using the Hair formula and taken using a non-probability sampling technique. This study used a quantitative approach with data collection through questionnaires. The data obtained were analyzed using multiple linear regression and Moderate Regression Analysis (MRA), which were then analyzed using the SPSS data processing program. The results showed that halal brand awareness and halal label had a positive and significant effect on the purchase decision of Saudi Store in Banda Aceh City. The results of this study indicate that religiosity acts as a pure moderating variable in the relationship between halal brand awareness and purchase decision where the interaction of religiosity strengthens the influence of halal brand awareness on purchase decision. Then the results of this study show that religiosity plays a role as a pure moderating variable in the relationship between halal labels and purchase decisions among Saudi Store consumers in Banda Aceh City, but the interaction of religiosity weakens the influence of halal labels on purchase decisions.